No evidence for an effect of selective spatial attention on the development of secondary hyperalgesia: A replication study - Della Porta, Delia; Vilz, Marie-Lynn; Kuzminova, Avgustina; Filbrich, Lieve; Mouraux, André; Legrain, Valéry (Frontiers in Human Neuroscience, 2022)
Central sensitization refers to the increased responsiveness of nociceptive neurons in the central nervous system after repeated or sustained peripheral nociceptor activation. It is hypothesized to play a key role in the development of chronic pain. A hallmark of central sensitization is an increased sensitivity to noxious mechanical stimuli extending beyond the injured location, known as secondary hyperalgesia. For its ability to modulate the transmission and the processing of nociceptive inputs, attention could constitute a promising target to prevent central sensitization and the development of chronic pain. It was recently shown that the experimental induction of central sensitization at both forearms of healthy volunteers using bilateral high-frequency electrocutaneous stimulation (HFS), can be modulated by encouraging participants to selectively focus their attention to one arm, to the detriment of the other arm, resulting in a greater secondary hyperalgesia on the attended arm as compared to the unattended one. Given the potential value of the question being addressed, we conducted a preregistered replication study in a well-powered independent sample to assess the robustness of the effect, i.e., the modulatory role of spatial attention on the induction of central sensitization. This hypothesis was tested using a double-blind, within-subject design. Sixty-seven healthy volunteers performed a task that required focusing attention towards one forearm to discriminate innocuous vibrotactile stimuli while HFS was applied on both forearms simultaneously. Our results showed a significant increase in mechanical sensitivity directly and 20 minutes after HFS. However, in contrast to the previous study, we did not find a significant difference in the development of secondary hyperalgesia between the attended vs. unattended arms. Our results question whether spatial selective attention affects the development of secondary hyperalgesia. Alternatively, the non-replication could be because the bottom-up capture of attention caused by the HFS-mediated sensation was too strong in comparison to the top-down modulation exerted by the attentional task. In other words, the task was not engaging enough and the HFS pulses, including those on the unattended arm, were too salient to allow a selective focus on one arm and modulate nociceptive processing.